Using cross-talk simulation to predict the performance of anaglyph 3-D glasses - Woods, Andrew J.; Harris, C. (JSID, 2012)
The anaglyph 3-D method is a widely used technique for presenting stereoscopic 3-D images. Its primary advantage is that it will work on any full-color display (LCDs, plasmas, and even prints) and only requires that the user view the anaglyph image using a pair of anaglyph 3-D glasses with usually one lens tinted red and the other lens tinted cyan (blue plus green). A common image-quality problem of anaglyph 3-D images is high levels of cross-talk — the incomplete isolation of the left and right image channels such that each eye sees a “ghost” of the opposite perspective view. An anaglyph cross-talk simulation model has been developed which allows the amount of anaglyph cross-talk to be estimated based on the spectral characteristics of the anaglyph glasses and the display. The model is validated using a visual cross-talk ranking test which indicates good agreement. The model is then used to consider two scenarios for the reduction of cross-talk in anaglyph systems and finds that a considerable reduction is likely to be achieved by using spectrally pure displays. The study also finds that the 3-D performance of commercial anaglyph glasses can be significantly better than handmade anaglyph glasses.